PERSEPSI PENYANDANG DISABILITAS DAN STAKEHOLDER UNTUK MEMPROMOSIKAN DAN MENGEMBANGKAN KOMUNITAS INKLUSIF DI DIY DAN ASIA TENGGARA - Hanjarwati, Astri; Suprihatiningrum, Jamil; Aminah, Siti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
This research was conducted to investigate the perceptions of persons with disabilities and stakeholders regarding the promotion and development of Friendly and Inclusive Communities in Bantul Regency, DIY and Kendari City, Southeast Sulawesi. The study was designed using transformative mixed-method, with the framework of KIPA (Knowledge, Inclusion, Participation, and Access) as a theoretical framework core. The first step was carried out by an empirical survey through distributing questionnaires to 48 respondents in Bantul Regency and 52 respondents in Kendari City. The results of data analysis from questionnaire contents were processed through descriptive statistics to describe respondents' perceptions quantitatively. Quantitative results are used as a reference in qualitative data collection, namely through in-depth interviews with selected respondents. The results of the study show that both persons with disabilities and stakeholders have a positive perception of the promotion and development of a friendly and inclusive community in their area. Although knowledge about disability, inclusion and the issues that surround it is still limited, but both persons with disabilities and stakeholders claim the need for a Friendly and Inclusive Community to be realized. Repondents of persons with disabilities also added that participation and access to development by and for persons with disabilities needs to be improved both in terms of quantity and quality.Penelitian ini dilakukan untuk menginvestigasi persepsi penyandang disabilitas dan stakeholders mengenai promosi dan pengembangan Komunitas Ramah dan Inklusif di Kabupaten Bantul, DIY dan Kota Kendari, Sulawesi Tenggara. Penelitian didesain menggunakan transformative mixed-method, dengan kerangka KIPA (Knowledge, Inclusion, Participation, and Access) sebagai core theoretical framework. Langkah pertama dilakukan dengan survey empiris melalui penyebaran kuesioner kepada 48 responden di Kabupaten Bantul dan 52 responden di Kota Kendari. Hasil analisis data dari isian kuesioner diolah melalui statistik deskriptif untuk menggambarkan persepsi responden secara kuantitatif. Hasil kuantitatif dijadikan sebagai rujukan dalam pengambilan data secara kualitatif, yaitu melalui in-depth interview kepada responden terpilih. Hasil penelitian menunjukkan baik penyandang disabilitas maupun stakeholders memiliki persepsi yang positif terhadap promosi dan pengembangan Komunitas Ramah dan Inklusif di daerah mereka. Meskipun pengetahuan mengenai disabilitas, inklusi dan isu-isu yang melingkupinya masih terbatas, namun baik penyandang disabiltias dan stakeholders mengaku perlunya Komunitas Ramah dan Inklusif untuk diwujudkan. Reponden penyandang disabilitas juga menambahkan bahwa partisipasi dan akses pembangunan oleh dan untuk penyandang disabilitas perlu ditingkatkan baik dari segi kuantitas maupun kualitas.